2013
DOI: 10.1093/ntr/ntt212
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smokers’ Use of Unconventional Tobacco Products and Associations With Quitting Activity: Findings From the ITC-4 U.S. Cohort

Abstract: The purpose of this study was to evaluate the prevalence and correlates of use of nicotine-containing tobacco products such as cigars, pipe tobacco, and cigarettes that promise less exposure to toxins; e-cigarettes; and smokeless tobacco products among a cohort of conventional cigarette smokers followed over the past decade. We also evaluated associations between use of such products and cigarette quitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
3
40
3
Order By: Relevance
“…Interestingly, we found that knowledge of waterpipe tobacco health warnings was a significant independent predictor of multiple use, and highly correlated with a positive change in the waterpipe smoking habits of participants (reduction in the number of hagar smoked, foregoing a smoke, being more likely to consider quitting). Multiple users in this case may have shifted to other tobacco products in an attempt to quit or because they were under the impression that they were smoking a "lighter" form of tobacco (20)(21)(22). We also found that the use of flavoured tobacco did not predict multiple use, as also reported in a US study (11).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, we found that knowledge of waterpipe tobacco health warnings was a significant independent predictor of multiple use, and highly correlated with a positive change in the waterpipe smoking habits of participants (reduction in the number of hagar smoked, foregoing a smoke, being more likely to consider quitting). Multiple users in this case may have shifted to other tobacco products in an attempt to quit or because they were under the impression that they were smoking a "lighter" form of tobacco (20)(21)(22). We also found that the use of flavoured tobacco did not predict multiple use, as also reported in a US study (11).…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, e-cigarettes were commonly used by multiple users in other studies (6,8,12,13). The use of non-cigarette products among cigarette smokers is thought to be an attempt to quit (20)(21)(22) but there are concerns that they may serve as an entry to cigarette use in young people (34). However, we did not examine the order in which Unique to our study, we asked participants about their awareness of the existing waterpipe tobacco health warnings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings demonstrate that current cigarette smokers are more likely to be aware of and to have used snus. These results could suggest the potential for dual use of snus and cigarettes, which poses a challenge for public health efforts to reduce tobaccoassociated morbidity and mortality (Kasza et al, 2013;Lee, Hebert, Nonnemaker, & Kim, 2014;Popova & Ling, 2013b). These results could also imply that current smokers may be interested in switching to snus if they hold certain perceptions of snus compared with cigarettes.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] Use of electronic cigarettes (e-cigarettes), cigars, smokeless tobacco, and hookah (waterpipe) has risen sharply in the past decade, [12][13][14][15] and the use of two or more tobacco products has increased in recent years, especially among young adults. [16][17][18][19] The Family Smoking Prevention and Tobacco Control Act of 2009 gave the Food and Drug Administration (FDA) broad regulatory authority over the manufacture, marketing, and distribution of regulated tobacco products to protect the health of the U.S. population. 20 The FDA Center for Tobacco Products uses a robust scientific evidence base to inform and assess the effect of its tobacco regulatory activities.…”
mentioning
confidence: 99%